2013 IEEE International Electron Devices Meeting 2013
DOI: 10.1109/iedm.2013.6724745
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach for trap-aware device/circuit co-design in nanoscale CMOS technology

Abstract: In this paper, the major physical effects caused by gate oxide traps in MOSFETs have been integrated for the first time by a proposed unified approach in realistic manners based on industry-standard EDA tools, aiming at practical trap-aware device/circuit co-design. The recently-found AC or transient effects of traps and the interplays with manufacturing process variations are included, with demonstrations on two representatives (RO and SRAM) under realistic digital circuit operations. The proposed approach an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In the device domain, recent studies have demonstrated that BTI and RTN, along with the random trap fluctuation (RTF), are consistently correlated with the physical trapping/detrapping effects of gate oxide traps as shown in Figure 13(b) [117]. In the nanometer scale, NBTI effects have shifted from deterministic degradations to stochastic ones due to limited number of gate oxide traps within each device [132][133][134][135].…”
Section: Design For Reliability (Dfr)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the device domain, recent studies have demonstrated that BTI and RTN, along with the random trap fluctuation (RTF), are consistently correlated with the physical trapping/detrapping effects of gate oxide traps as shown in Figure 13(b) [117]. In the nanometer scale, NBTI effects have shifted from deterministic degradations to stochastic ones due to limited number of gate oxide traps within each device [132][133][134][135].…”
Section: Design For Reliability (Dfr)mentioning
confidence: 99%
“…Examples of lithography hotspots[112]. Color online) (a) Stacking effect in NOR gate; (b) various reliability/variability issues induced by gate oxide traps[117].…”
mentioning
confidence: 99%
“…Based on our newly proposed method [17], the approach for accurate simulation of RTN effects in digital circuits is shown in Fig. 6.…”
Section: A Ac Rtn Vs DC Rtn: Silicon Evidence and Modelingmentioning
confidence: 99%
“…In particular, bias temperature instability (BTI) stresses reduce the read margin of the SRAM cell and affect its stability, leading to possible read fails [6]. So far this concern has been investigated either by simulations or by conventional measurements [7]- [9] of the read static noise margin (RSNM) degradation using the well-known butterflycurve technique [10]. However, using this slow two-steps technique leads to inaccurate characterization of the dynamic variability in SRAM cells.…”
Section: Introductionmentioning
confidence: 97%